Women's right to freedom of expression in the Holy Quran and the Prophetic Sunnah: A foundational study - Ahmed, Dr. Aso Reda (Sulaimani Journal for Humanities, 2026)
This research sheds light on women's right to freedom of expression, drawing upon two primary sources: the Holy Quran and the Sunnah (Prophetic traditions). It aims to dispel the doubts of those who deny women this right to express their opinions and participate in all aspects of life. The research presents examples of women who freely expressed their views. By documenting these stances in the Quran and Sunnah, this right becomes an undeniable reality.